MENCARI HUBUNGAN POSITIF ANTARA PENINGKATAN KESEJAHTERAAN GURU BAHASA INGGRIS BAGI YANG BERSERTIFIKASI TERHADAP PENINGKATAN MUTU PEMBELAJARAN DALAM KELAS SE-KOTA BANJARBARU - Listia, Rina; Mu’in, Fatchul; Yamin, Moh. (Vidya Karya Jurnal Kependidikan, 2013)
This research focuses on the effect of teachersâ high income (teachersâ sertificate) for English teachers to increase the quality of teaching in the classroom. It is found that the teachers with sertificate in Banjarbaru always-often (<60%) try to understand the studentsâ potency and characteristics. Generally, teachers in state junior high school, state senior high school, and vocational high school have mastered the theories and the principles of teaching effectively. However, the advantage of high income from teachersâ sertificate does not give the positive effect to increase their capacities as professional teachers. The consciousness of teachersâ performance after getting high income from teachersâ sertificate is not relatively satisfying. The teacherâs performance to take part in education and training and to buy complementary books for capacity building is not satisfying.